2020
DOI: 10.48550/arxiv.2009.03347
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kaluza-Klein Spectrometry from Exceptional Field Theory

Emanuel Malek,
Henning Samtleben

Abstract: Exceptional field theories yield duality-covariant formulations of higher-dimensional supergravity. They have proven an efficient tool for the construction of consistent truncations around various background geometries. In this paper, we demonstrate how the formalism can moreover be turned into a powerful tool for computing the Kaluza-Klein mass spectra around these backgrounds. Most of these geometries have little to no remaining symmetries and their spectra are accessible to standard methods only in selected… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
68
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(71 citation statements)
references
References 62 publications
(159 reference statements)
2
68
0
1
Order By: Relevance
“…[10], used to be notoriously difficult. However, within the last year, a new and powerful method based on Exceptional Field Theory (ExFT) [11] was developed in [12,13] for computing Kaluza-Klein spectra of vacua of maximal gauged supergravities. At the same time, [14] showed that probe branes can be used to easily search for signals, dubbed brane-instabilities, of non-perturbative instabilities [10].…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…[10], used to be notoriously difficult. However, within the last year, a new and powerful method based on Exceptional Field Theory (ExFT) [11] was developed in [12,13] for computing Kaluza-Klein spectra of vacua of maximal gauged supergravities. At the same time, [14] showed that probe branes can be used to easily search for signals, dubbed brane-instabilities, of non-perturbative instabilities [10].…”
mentioning
confidence: 99%
“…In [12,13], ExFT was used to derive mass matrices for the Kaluza-Klein spectrum around any vacuum of N = 8 gauged supergravities in four and five dimensions that arises from a consistent truncation of 10-/11-dimensional supergravity. Let us briefly review some of the salient features of ExFT and Kaluza-Klein spectroscopy.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, it is encoded in a group-valued Scherk-Schwarz twist matrix living on the duality group of the lowerdimensional theory. This formulation moreover allows a straightforward access to computing the entire Kaluza-Klein spectrum around any background living within the consistent truncation [12,13].…”
mentioning
confidence: 99%